Gunther Schuller: A life in pursuit of music and beauty - Schuller, Gunther (Rochester Boydell & Brewer, 2011)
Simultaneously the memoir of a famed composer, conductor, and music educator, and an important historical sourcebook on the American musical scene during the twentieth century and into the twenty-first, the autobiography of Gunther Schuller chronicles the first thirty-five years of this multifaceted and expansive figure's life and work. Schuller began composing music at an early age and joined the Cincinnati Symphony as its principal French horn player at seventeen. Since then he has written for many major orchestras and his work has earned him a MacArthur Foundation "genius" grant and the Pulitzer Prize in 1994 for his large-scale orchestral piece Of Reminiscences and Reflections. Perhaps most famously, Schuller contributed to a new stylistic blend between progressive factions of jazz and classical music, for which he coined the term "Third Stream," and collaborated with John Lewis, the Modern Jazz Quartet, and others in the development of this style. In this exquisitely detailed reflection on his early influences, experiences of good fortune, and powers of curiosity, as well as firsthand recounting of critical cultural and social moments and major movers of the jazz world, Schuller here beautifully and honestly narrates a life lived beyond limits. Gunther Schuller has been on the faculties of the Manhattan School of Music and Yale University; he was, for many years, head of contemporary music activities (succeeding Aaron Copland) and director of the Tanglewood Music Center, and served as president of the New England Conservatory. He is the author of The Swing Era: The Development of Jazz, 1930-1945; Early Jazz: Its Roots and Musical Development; The Compleat Conductor, and many other books.